ANALISIS PERANAN GURU PAUD TERHADAP PROSES PEMBELAJARAN ANAK PADA MASA PANDEMI (COVID-19) USIA 4-5 TAHUN TK POETEUMEUREHOM BANDA ACEH - Diani, Meli; Nurtiani, Ayi Teir; Zamana, Millata (Jurnal Ilmiah Mahasiswa Pendidikan, 2021)
The online learning system (in a network) is a learning system without face-to-face learning between teachers and children but is carried out online using an internet network, in the implementation of learning collaboration between teachers and parents of students is required. The research objective was to analyze the implementation of online learning during the Covid-19 pandemic at Poteumeurehom Kindergarten and to describe the obstacles faced by teachers in implementing online learning during the Covid-19 pandemic at Poteumeurehom Kindergarten. This type of research is qualitative research with a case study design. The research subjects of group B teachers were 6 people, data were collected through interviews and documentation. Data analysis uses qualitative analysis techniques, the Miles & Huberman model, including data reduction, display data, and conclusion drawing / verification. The results showed that the implementation of online learning was carried out through the WhatsApp application with the steps of planning online learning activities, implementing online learning and evaluating online learning. In planning activities, the Covid 19 emergency RPPH was compiled, online schedules, making groups for each group B. In implementation activities include greeting and sharing material. In the evaluation activities the teacher checks the children's activities sent by the parents, both in the form of photos, videos and voicenotes which are then included in daily assessments, weekly assessments and semester assessments. The obstacles faced in online learning during the Covid-19 era at TK Poteumeurehom include the absence of interaction between teachers and students because they only use the WhatsApp application, parental unpreparedness, communication between teachers and parents and also constrained by the availability of information technology devices owned by parents. Abstrak Sistem pembelajaran daring (dalam jaringan) merupakan sistem pembelajaran tanpa tatap muka secara langsung antara guru dan anak tetapi dilakukan melalui online yangmenggunakan jaringan internet, dalam pelaksanaan pembelajaran diperlukakan kerjasamaantara guru dan orangtua murid. Tujuan penelitian untuk menganalisis pelaksanaanpembelajaran daring pada masa pandemi Covid-19 di TK Poteumeurehom dan untukmendeskripsikan kendala yang dihadapi guru dalam pelaksanaan pembelajaran daringpada masa pandemi Covid-19 di TK Poteumeurehom. Jenis penelitian yang digunakanadalah penelitian kualitatif dengan desain studi kasus. Subjek penelitian guru kelompok Bsebanyak 6 orang, data dikumpulkan melalui wawancara dan dokumentasi. Analisis datamenggunakan teknik analisis kualitatif model Miles & Huberman meliputi data reduction,data display, dan conclusion drawing/verification. Hasil penelitian menunjukkan bahwapelaksanaan pembelajaran daring dilakukan melalui aplikasi WhatsApp dengan langkahmenyusun perencanaan kegiatan pembelajaran daring, pelaksanaan pembelajaran daringdan evaluasi pembelajaran daring. Dalam kegiatan perencanaan disusun RPPH daruratCovid 19, jadwal daring, membuat group masing-masing kelompok B. Dalam kegiatanpelaksanaan meliputi kegiatan menyapa dan sharing materi. Dalam kegiatan evaluasi gurumemeriksa kegiatan anak yang dikirim oleh orangtua, baik dalam bentuk foto, video, danvoicenote yang selanjutnya dimasukan dalam penilan harian, penilaian mingguan danpenilaian semesteran. Kendala yang dihadapi dalam pembelajaran daring pada masa Covid19 di TK Poteumeurehom diantaranya tidak adanya interaksi antara guru dengan muridkarena hanya menggunakan aplikasi WhatsApp saja, ketidaksiapan orangtua, komunikasiantara guru dengan orangtua dan juga terkendala oleh ketersediaan perangkat teknologiinformasi yang dimiliki orangtua.